Contrato social e (Des)igualdade - Hemerson Luiz Pase (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2008)
The article discusses the social contract through a theoretical perspective that reveals the limits of the category of equality to guide the action the contemporary state. The company is uneven and, if you want to overcome this condition, you need to sue the state treats the different uneven, namely, public policies need to be targeted with a view to enabling those social segments historically positioned precariously, acquiring conditions, become equal, For being able to contest the general policies. Democratic participation, materialized through mechanisms such as participatory budgeting, has conditions to create a public space for debate and influence the state to act unequally in favor of the most disadvantaged.